2011
DOI: 10.1089/end.2010.0303
|View full text |Cite
|
Sign up to set email alerts
|

Management of Complete Ureteral Avulsion and Literature Review: A Report on Four Cases

Abstract: Complete ureteral avulsion is a rare but severe complication. Autotransplantation of kidney and ureterovesical anastomosis may result in positive outcomes in patients with proximal ureteral avulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Among all complications of ureteroscopic lithotripsy procedure, complete avulsion of the proximal ureter is one of the most challenging that happens in 0.06–0.45% of the cases [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Among all complications of ureteroscopic lithotripsy procedure, complete avulsion of the proximal ureter is one of the most challenging that happens in 0.06–0.45% of the cases [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Among these complications, ureteral avulsion is the most severe and challenging condition to manage and occurs in 0.06e0.45% of cases. 1 One of the most frequently reported causes of complete ureter avulsion was stone manipulation with a basket. 2 However, the immediate cause of ureter avulsion in the above cases was narrowing of the ureteral lumen.…”
Section: Discussionmentioning
confidence: 99%
“…14 Other possible techniques used for ureteral reconstruction include psoas hitch, Boari flap, or a combination of both, ileal interposition, transureteroureterostomy, permanent nephrostomy, appendix or colon interposition, renal descensus, ureterocalicostomy, and pyeloureterostomy plus greater omentum investment outside the avulsed ureter, if these modalities are not possible than as a last resort nephrectomy may have to be performed. 4,6,[14][15][16][17][18] due to the use of small caliber endoscopes the long term complication of uretreic stricture is not frequently observed and can be expected in less than 1% of the patients. 19 However in our study no case of post operative/iatrogenic stricture was identified with a minimum follow up period of one year.…”
Section: Figure-1 Increase In Number Of Cases Managed By Ureterorenomentioning
confidence: 99%